Relationship between Workload and Work Fatigue in Employees of Company’s Production Department - Rambe, Desi; Utami, Tri Niswati; Arrazy, Syafran (Newinera Publisher, 2024)
The role of human resources is very important to carry out work processes and achieve company goals. So that the role of employees can run optimally, companies need to pay attention to factors that influence worker fatigue, including internal factors (age, gender, nutritional status and psychological state of the workforce) and external factors (workload, length of service and physical work environment). Workload is divided into two, namely mental workload and physical workload. Mental workload is a human evaluation of attention limits while carrying out tasks optimally which is influenced by the workload demands of a task. The population in this study was 127 employees with a sample of 83 respondents. Based on the results of the chi square statistical test, a p value of 0.001<0.005 was obtained. Results from research There is a significant relationship between mental workload and work fatigue in production employees. It is recommended to PT. Milano should pay attention to the conditions of his workers.